2016
DOI: 10.3390/fib4010006
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Fiber-Reinforced Mortars Incorporating Nano-Silica

Abstract: Repair and rehabilitation of deteriorating concrete elements are of significant concern in many infrastructural facilities and remain a challenging task. Concerted research efforts are needed to develop repair materials that are sustainable, durable, and cost-effective. Research data show that fiber-reinforced mortars/concretes have superior performance in terms of volume stability and toughness. In addition, it has been recently reported that nano-silica particles can generally improve the mechanical and dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 40 publications
3
39
0
Order By: Relevance
“…However, concrete also has disadvantages such as a low tensile strength, poor toughness, and high brittleness, which adversely affect the safety, applicability, and durability of the concrete structure [2]. Many studies have shown that the mechanical properties and durability of concrete can be effectively improved by incorporating fibers into it, thus obtaining fiber-reinforced concrete for high strength, toughness, and durability [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, concrete also has disadvantages such as a low tensile strength, poor toughness, and high brittleness, which adversely affect the safety, applicability, and durability of the concrete structure [2]. Many studies have shown that the mechanical properties and durability of concrete can be effectively improved by incorporating fibers into it, thus obtaining fiber-reinforced concrete for high strength, toughness, and durability [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Li, 2003;Li et al, 2010;Lepech and Li, 2010;Zhu, 2013). More recently, FRCC has been developed using high performance cementitious matrices incorporating nanosilica particles (Ghazy et al 2016a, Mahmoud et al 2017 for various infrastructure applications.…”
Section: Introductionmentioning
confidence: 99%
“…The deflection ductility of a brittle matrix (such as cement mortar) is improved with the addition of discontinuous fibres [17] and its flexural ductile behavior gives early warning signs aiding in the prevention of sudden, unexpected, and catastrophic failures of the structural elements in question [18]. Deflection ductility of a structural element (slab, beam) is determined by experiments employing simple flexural tests [17][18] based on mid-span deflection [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Deflection ductility of a structural element (slab, beam) is determined by experiments employing simple flexural tests [17][18] based on mid-span deflection [19][20][21]. Previous studies [1], [5], [10][11][12], [22][23] have shown that deflection ductility behavior is characterized by the ability to sustain higher levels of loading after the first cracking while undergoing a large deformation [17]. The deflection ductility at the first crack and the ultimate load bearable in cement-based composites depends upon element thickness, type of reinforcement (mesh and/ or fibres), and the volume fraction (percentage) of mesh and fibres [1], [10][11][12].…”
Section: Introductionmentioning
confidence: 99%